2023
DOI: 10.1097/qad.0000000000003506
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive disorders of pregnancy and HIV: analysis of a province-wide cohort during 2018 and 2019

Abstract: Objective: We evaluated the prevalence of de novo hypertensive disorders of pregnancy (dnHDP) in pregnant people with HIV (PPHIV) in the Western Cape Province, South Africa in 2018–2019 by HIV and antiretroviral therapy (ART) status. Methods: All people with a pregnancy outcome from 1 January 2018 to 31 December 2019 in the Western Cape Provincial Health Data Centre (WCPHDC) were included. The WCPHDC integrates data from multiple electronic platforms according to unique ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
2
1
Order By: Relevance
“…Consequently, there may be an increased likelihood of misdiagnosing severe forms of hypertension in pregnancy such as HELLP syndrome and preeclampsia. This is in contradiction to a study which concluded long term ART could be protective in hypertensive disorders in pregnancy 16 . Unfortunately, there is a lack of data on the type of hypertension and Vol 12.…”
Section: Discussioncontrasting
confidence: 97%
“…Consequently, there may be an increased likelihood of misdiagnosing severe forms of hypertension in pregnancy such as HELLP syndrome and preeclampsia. This is in contradiction to a study which concluded long term ART could be protective in hypertensive disorders in pregnancy 16 . Unfortunately, there is a lack of data on the type of hypertension and Vol 12.…”
Section: Discussioncontrasting
confidence: 97%
“…Our finding that the risk of elevated blood pressure in pregnancy did not differ by HIV status largely aligns with previous literature on HIV and hypertensive disorders in pregnancy [ 21 , 58–60 ], including a recent population-based cohort study form the Western Cape province in South Africa [ 61 ]. While these findings are reassuring, the fact that a third of the cohort had elevated blood pressure or higher postpartum is concerning.…”
Section: Discussionsupporting
confidence: 89%
“…This was a province-wide retrospective cohort study of pregnant people delivering from 1 January 2018 to 31 December 2019 at all 54 public sector healthcare facilities that provide obstetric delivery services in the Western Cape. Algorithms used by the WCPHDC to identify pregnancy, the identification of this specific 2018–2019 maternity cohort and classification of dnHDP have been described [ 20 , 21 ]. For this analysis, the cohort was restricted to the first viable (i.e.…”
Section: Methodsmentioning
confidence: 99%